Investigating factors influencing the adoption and use of Free and Open Source Software (FOSS) in Tanzanian higher learning institutions: towards an Individual-Technology-Organizational-Environmental (ITOE) framework - Kisanjara, Simeo; Tossy, Titus (International Journal of Research in Business and Technology, 2024)
Article published by the International Journal of Research in Business and Technology Volume 5, Issue 2, Pages 645-653